PENGARUH LINGKUNGAN KERJA FISIK DAN NON FISIK TERHADAP KINERJA PEGAWAI PADA BADAN KETAHANAN PANGAN DAN PELAKSANA PENYULUHAN DAERAH KOTA SAMARINDA - Mashul Akbar Sukamto (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purposde of this article is to explain the influence of work environment to employee performance. It was a work achievement, it is very nessecity in supporting organization mission. So that is why, it need some pull factor to improve employee performance. The result show that Farm Resilience Department need to create a condusive situation for increasing employee performence.